PENGEMBANGAN MODUL PRAKTIKUM STRUKTUR HEWAN BERBASIS GUIDED INQUIRY - Maspupah, Meti; Subandi, Muhammad (Jurnal BIOEDUIN, 2019)
This research aimed is to develop a Practicum Module. Animal Structure Practicum Module has undergone several trials namely the first Practicum Module trial, small scale Practicum Module trial and the final Practicum Module trial. In the first Practicum Module trial, the Practicum Module was validated by expert in Biology Education, UIN SGD Bandung, then tested to ten student. and at the final practicum module trial, the developed modules began to be applied in classroom. The instuments used were validation questionnaire, and response questionnaire. After going through the process of data analysis, the result of the study show : Preparation of the Animal Sructure Practicum Module based on the Guided Inquiry using Analysis model, Development, Design, Implementation and Evaluation (ADDIE) at the development stage with an average score 0,88 with valid categories and validation with an average score 0,98 with valid categories, thus this Practicum Module can be implemented when learning in classroom. Student responses to the use of Practicum Module based on Guided Inquiry that developed in the study of animal structure showed a positive response. This is based on the analysis of student response questionnaires with an average score 3,64 with high classification.